Between two wars? : the lessons of the last World War in relation to the preparations for the next - Vigilantes; Zilliacus, Konni (Harmondsworth : Penguin, 1939)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 1; Wereldoorlog 2; politieke geschiedenis; Groot-Brittannië.